Two new wolf-spider species in the genus Hippasosa from Asia (Araneae, Lycosidae) - Lu-Yu Wang; Muhammad Irfan; Zhi-Sheng Zhang (ZooKeys)
Two new species of the wolf-spider genus Hippasosa Roewer, 1960 are described from Asia: Hippasosa thailandica sp. nov. (♂) from Thailand and H. yunnanensis sp. nov. (♂♀) from China. Detailed species descriptions, morphological photographs, genitalia illustrations, and distribution maps of the new species are presented. Photographs of H. qiongzhongensis (Yin & Peng, 1997) are also provided for comparison purposes.